Perceived Value of Patients with Intention to Revisit at Health Facilities: A Scoping Review - Kristanti Diliasari; Dumilah Ayuningtyas (International Journal of Social Service and Research, 2023)
Background. Perceived value is a subjective aspect of customers that has an important influence on their repurchase behavior. Perceived customer value makes a major contribution to the possibility of customers continuing to recommend services to others so that they become a valuable commodity. Objective. This study examines the relationship between patient perceived value and intention to revisit health facilities. Method. This scoping review was carried out by searching 4 health databases, namely PubMed, EbscoHost, Google Scholar, and Garuda Portal with a time limit of the last 10 years. Results. Based on the 8 included articles, the relationship between perceived value and patient visit intentions can be direct or indirect with other variables as mediators. Conclusions and Recommendations. Hospitals and health facilities need to include aspects of patient perceived value in addition to service quality in maintaining patient loyalty and the future of health facilities amidst increasing competition.